Prenatal exposure to inflammation increases anxiety-like behaviors in F1 and F2 generations: possible links to decreased FABP7 in hippocampus - Chen, Jing; Zhang, Zhe-Zhe; Luo, Bao-Ling; Yang, Qi-Gang; Ni, Ming-Zhu; Wu, Qi-Tao; Li, Yun; Li, Xue-Wei; Chen, Gui-Hai (Frontiers in Behavioral Neuroscience, 2022)
Anxiety disorder has a high prevalence, and the risk of anxiety increases with age. Prenatal inflammation during key developmental timepoints can result in long-term changes of anxiety phenotype, even over a lifetime and across generations. However, whether maternal inflammation exposure during late gestation has intergenerational transmission effects on age-related anxiety-like behaviors and the possible underlying mechanisms are largely unknown. Fatty acid binding protein 7 (FABP7) is critical in hippocampal neurogenesis and closely related to neuropsychiatric diseases, including anxiety disorder. The current study investigated the effects of maternal (F0 generation) lipopolysaccharide administration (50 μg/kg, i.p.) during late gestation on anxiety-like behaviors and FABP7 expression in F1 and F2 offspring, as well as the potential sex-specificity of intergenerational effects. Anxiety-like behaviors were evaluated using open field, elevated plus maze, and black–white alley tests at 3 and 13 months of age. The protein and messenger RNA levels of FABP7 in the hippocampus were measured using western blot and real-time quantitative polymerase chain reaction, respectively. Our findings showed that maternal LPS exposure during late gestation could increase anxiety levels and decrease FABP7 expression levels in F1 and F2 offspring, and the intergenerational effects were mainly transferred via the maternal lineage. Moreover, hippocampal FABP7 expression was significantly correlated with performance in the battery of anxiety tests. The present study suggested that prenatal inflammation could increase age-related anxiety-like behaviors both in the F1 and F2 generations, and these effects possibly link to the FABP7 expression.